Comparing membrane sweep and cervical massage in preventing the need for formal labour induction in uncomplicated pregnancy at term: Secondary analysis of a randomized controlled trial. - Thennakoon Mudiyanselage Salila Sameera Bandara Madugalle; Dissanayaka Mudiyanselage Chandana Sirimewan Jayasundara; Indu Asanka Jayawardane (PLoS ONE, 2025)
Introduction Any intervention aimed at maximizing the spontaneous onset of labor and preventing formal induction will be beneficial to the client and welcomed by the provider, because it reduces postmaturity and formal labour induction. Methods We recruited and randomized 312 uncomplicated singleton pregnancies at 38 weeks of gestation into three groups: membrane sweep (MS), cervical massage (CM), and sham sweep (control). Each intervention was administered at 39 weeks and repeated at 40 weeks of gestation if spontaneous labor, defined as a Modified Bishop's Score of ≥7, did not occur. (Sri Lanka clinical trials registry - SLCTR/2020/003). Results The membrane sweep reduced the need for formal induction, whereas cervical massage did not. (MS vs C RR = 1.4195, 95% CI = 1.0326-1.9513, p = 0.0310; MS vs C OR=1.8739, 95% CI = 1.0664-3.2927, p = 0.0290; Number Needed to Treat = 7; CM vs C RR = 1.2043, 95% CI = 0.8598-1.6867, p = 0.2795). "Survival without spontaneous labor," was lower after the membrane sweep than in controls overall (MS vs C - p = 0.007; CM vs C - p = 0.261), among primiparous (MS vs C p = 0.047; CM vs C p = 0.269) and multiparous (MS vs C p = 0.038; CM vs C p = 0.456) women. The membrane sweep and cervical massage were safe concerning feto-maternal complications and both reduced hospital-stay duration among multiparous women (MS vs C p < 0.0001, 95% CI = 0.5293-1.1791; CM vs C p < 0.0001, 95% CI = 0.6816-1.3552). There was no increased risk of emergency cesarean delivery, oxytocin augmentation, uterine hyperstimulation, postpartum bleeding, maternal pyrexia, or Apgar score < 7 at 5 minutes (p > 0.05). The membrane sweep was less acceptable compared to cervical massage, regardless of parity (MS vs C Primi p = 0.001, Multi p = 0.0216). Conclusion and recommendations We recommend routine offer of membrane sweep to reduce the need for formal induction in term uncomplicated pregnancies, but clinicians should be aware of its inherent discomfort to women.